Homoseksual dalam al-Qur'an: Analisis Semantik Frase Ghairu Ulil Irbah dalam Surat An-Nur ayat 31 - Ali Qorror Al Khasy (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2019)
There is a phrase in the Qurâ€™an called â€˜ghairu ulil irbahâ€™ which represents individuals who tend to have a non-hetero sexual orientation. This phrase is also mentioned in Surah An-Nur verse 31, so the researcher review this phrase because some people misunderstand with it. Therefore, this study aims to explain the meaning of ghairu ulil irbah, the semantic implication of ghairu ulil irbah in sexual orientation point of view and the further definition of ghairu ulil irbah based on the context of Surah An-Nur verse 31.There are three steps in this language research: providing data, data analysis; the data will be analyzed by using identity and contextual method, and presentation of analysis result in descriptive report.The result shows that the underlying meaning of the word irbah from the phrase ghairu ulil irbah is â€œnecessityâ€. In particular cases, the word irbah has narrowed meaning but do not change the meaning itself. Thus, it can be said that the relational meaning of irbah is sexual needs of someoneâ€™s sexual desire, specifically, ghairu ulil irbah stays in the context of â€˜sexualâ€™. It was different from peopleâ€™s interpretations several years ago said that ghairu ulil irbah dealt with people who lose their minds. It is interesting to note that this phrase focuses on the various sexual orientations because this term correlates with expressing a sexual desire to the sexual object.